The Categorical Imperatives of a United States of Africa in the Age of Global Economic Competition - Igbokwe-Ibeto, Chinyeaka Justine; Ozigbo, Ada Mac - (NIU Journal of Humanities, 2020)
Africa has found itself in the background of socio-economic, political and technological developments. Long before the European incursion into Africa, the continent was the credo of civilization in various fields of human endeavors. It took three epochal events: slavery, colonialism and neo-colonialism to lay the foundation for the penetration and exploitation of the African peoples and societies. It is against this background we must understand and appreciate the present marginalization and underdevelopment in the continent. These epochal events distorted and disoriented the continent and its people to the extent that presently it is one of the poorest continents in the world. Therefore, the clamor for and move towards a United States of Africa are long overdue and inevitable. It will pull resources together, give the people itself in themselves and their abilities to develop their own way and give the continent respect in the community of nations. The paper argued that, all these can only be realized if certain normative obstacles are removed. These include: the subservient role of some African leaders and would be leaders to international capitalists; opposition from the developed countries that may lose out if such adventure succeeds, scarcity of political and economic resources to achieve such enterprise. The paper concludes that, the goal of United States of Africa is realizable provided the necessary steps as mentioned are taken, sustained and achieved. Keywords: Economy, globalization, sustainability, progress, neo-colonialism